BUSINESS PROCESS REDESIGN OF DIGITAL LIBRARIES IN INDONESIA - Leo Barus (Scientia Integritas Utama, 2022)
The library visit interest of high and university students in Indonesia is underrated, so it is necessary to improve and increase the capabilities of digital libraries. By using a literature study, it was concluded that improving and increasing students' reading interest in Indonesia can be done by redesigning digital library business processes.